Design, synthesis and photo-cross-linking of a new photosensitive macromonomer from tetra-branched poly(ethylene oxide)s - Froimowicz, Pablo (2008)
A general procedure to increase the amount of photoreactive chromophore groups per oligoether chain is presented. In this work, a photoreactive macromonomer with four functionalities was synthesized by a four-step synthetic pathway with high yield. The photochemical behavior of this compound was studied with a view to obtaining polymeric networks. The significant advantage in this strategy is that the preparation of this material has as last operation, the obtaining and processing of polymer as thin film. In this way, the synthetic strategy based on assembling: (i) the polyether chains, (ii) a film forming backbone, and (iii) a photoactive moiety to be used for cross-linking, seems a viable solution to the problem of the continuous processing of materials.